βig-h3 enhances chondrogenesis via promoting mesenchymal condensation in rat Achilles tendon heterotopic ossification model - Zhang, Qiang (Aging (Albany NY), 2020)
Heterotopic ossification (HO) is a poorly characterized disease with ectopic bone formation in the musculoskeletal soft tissues. HO is widely considered as a tissue repair process goes away, with endochondral ossification to be the major pathological basis. The molecular mechanism of how the resident/recruited progenitor cells for tissue regeneration error differentiated into the chondrocytes remains unknown. Here, we found Transforming Growth Factor B Induced Gene Human Clone 3 (βig-h3) was highly expressed in the inflammation and chondrogenesis stages of a heterotopic ossification model after rat Achilles tendon injury, as well as upon chondrogenic differentiation conditions in vitro. βig-h3 functioned as an extracellular matrix protein, which was induced by TGFβ signaling, could bind to the injured tendon-derived stem cells (iTDSCs) and inhibit the attachment of iTDSCs to collagen I. Exogenous βig-h3 was also found able to accelerate the process of mesenchymal condensation of cultured iTDSCs and promote chondrogenic differentiation in vitro, and additional injection of iTDSCs could promote endochondral ossification in Achilles tendon injury model. Taken together, βig-h3 might function as an adhesion protein that inhibited the attachment of iTDSCs to collagen I (the injury site) but promoted the attachment of iTDSCs to each other, which resulted in promoting chondrogenic differentiation.